Atypical Dermatological Presentation of Multisystem Inflammatory Syndrome in a Child with Polyarticular JIA: A Case Report - Iman, Kazi; Akter, Laboni; Laila, Kamrul; Islam, Mohammad Imnul; Rahman, Shahana Akhter (Bangladesh Journal of Child Health, 2024)
Multisystem inflammatory syndrome in children (MIS-C) is an inflammatory process that occurs after infection with SARS-CoV-2 virus. In this syndrome children usually present with fever, rash, abdominal pain, diarrhea or vomiting, hypotension and shock. Children may need urgent care if heart, blood vessels or other vital organs are involved. Poly-articular Juvenile Idiopathic arthritis is a subset of JIA defined by presence of arthritis of five or more joints within 6 months of disease onset along with other criteria of JIA. In this case report we report mucocutaneous manifestation of MIS-C in a child with poly-articular rheumatoid factor (RF) negative JIA case. BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 86-88